THE MAIN SUCKING PESTS (HOMOPTERA, APHIDIDAE, ALEYRODIDAE, COCCOIDAE) OF THE ORNAMENTAL PLANTS ON THE ABSHERON PENINSULA OF AZERBAIJAN HELMINTH FAUNA OF THE STRIPED LIZARDS IN THE LENKORAN NATURAL AREAS - Z. M. Mamedov; E. F. Safarova (Юг России: экология, развитие, 2014)
About 36 species of sugescent pests (aphids, Chinese scales) do harm to the flowers and decorative plants in the gardens, parks, public garden, greenhouses and hothouses of Absheron, 17 types out them are dominating types. They mostly harm palms, ficus, oleander, laurel, asparagus, orchidea, cactus, agave, different types of roses and other decorative plants.There are state main sugescent pests of decorative plants of Absheron by mentioning the level of their popularity and their place of location in the article.